Cultural centers in the book of endowments of Mosul No. 169/1 "Bhdinan, Erbil and Sulaymaniyah as an example" A historical and documentary study - Younis, Majed (Humanities Journal of University of Zakho, 2021)
The Ottoman notebooks are regarded as important Ottoman records that are specialized in the study of endowments and endowment institutions. These notebooks contain important historical information for most of the vilayets that were ruled by the Ottoman Empire, manifesting an inventory of mosques, schools and hospices, even if all of them are not covered or comprehensively mentioned. In viewing these notebooks, valuable historical information is served, and the history of endowments, which include the names of the most remarkable religious and educational institutions and service facilities, is reflected. These notebooks and recordstackle the names of mosques, hospices, holy shrines, the names of institution administrators, the quality of their relationship with the ruling authorities, and the names of donators, whodeposited their money or property for serving these institutions. In this study, one of the Ottoman notebooks (the notebook of Mosul Vilayet) was chosen. For descriptive research purposed, the study was divided into three main sectionswith an introduction to the endowments and their importance in the Ottoman history, and a conclusion reached by the researcherthroughout the study. In the first section, titled “Behdinan in the Endowment Book of the Mosul Vilayet),the Mosul Vilayet and the date of its joining to the Ottoman state were clearly defined to briefly study the most important religious and scientific institutions. Also, focus is on the most significant endowments dedicated to serving these institutions with the endowers’ names and the notes related to them. In the second section, titled“Erbil and Sulaymaniyah in the Endowment Book of the Mosul Vilayet”, light was mainly shed on the most important religious and scientific institutions, the most significant endowmentsdevoted to serving these institutions, presenting the names and terms of the endowments, with some other minor details related to the study.